2022
DOI: 10.48550/arxiv.2205.05393
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CVTT: Cross-Validation Through Time

Abstract: The practical aspects of evaluating recommender systems is an actively discussed topic in the research community. While many current evaluation techniques bring performance down to a single-value metric as a straightforward approach for model comparison, it is based on a strong assumption of the methods' stable performance over time. In this paper, we argue that leaving out a method's continuous performance can lead to losing valuable insight into joint data-method effects. We propose the Cross-Validation Thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…To illustrate the performance of DIL over time, we use the example of LightGCN on the Amazon-books dataset and plot the Recall@20 scores over the four testing periods in Figure 5.4. It is observed that the ranking orders of the baselines vary across different periods, which aligns with findings in prior studies such as [18] on other datasets. This observation emphasizes the importance of monitoring evaluation results over time to avoid potential bias in a particular period.…”
Section: Effectiveness and Robustnesssupporting
confidence: 87%
See 3 more Smart Citations
“…To illustrate the performance of DIL over time, we use the example of LightGCN on the Amazon-books dataset and plot the Recall@20 scores over the four testing periods in Figure 5.4. It is observed that the ranking orders of the baselines vary across different periods, which aligns with findings in prior studies such as [18] on other datasets. This observation emphasizes the importance of monitoring evaluation results over time to avoid potential bias in a particular period.…”
Section: Effectiveness and Robustnesssupporting
confidence: 87%
“…Some studies have stressed the necessity of considering "time" factor in offline evaluation of recommender system [18][19][20]163]. The authors of [163] argue that a setting which strictly follow a global timeline is a more realistic setting for evaluation.…”
Section: Challenges In Evaluating a Recommender Systemmentioning
confidence: 99%
See 2 more Smart Citations